Heat Transfer on Rotating Second Grade Fluid Through an Accelerated Plate - Ahmad Qushairi, Mohamad; Khan, Ilyas; Lim, Yeou Jiann; Sharidan, Shafie; Zaiton, Mat Isa; Zulkhibri, Ismail (Penerbit UTM Press, 2017)
Heat transfer on an unsteady free convection rotating second grade fluid flow, which is flowing through an accelerated plate, is analyzed. The physical problem investigated is described by a coupled, linear system of partial differential equations, with appropriate boundary conditions. Laplace transform technique is applied to determine the analytical solutions of the dimensionless governing equations. The effects of various embedded parameters to the velocity and temperature distribution in the fluid are graphically illustrated and analyzed. The obtained analytical results constitute a good verification to verify a more advance situation of the physical problem, which is described by a non-linear system and only can be solved by using approximation method.